UJI EFEKTIFITAS ANTIBAKTERI EKSTRAK DAUN PEGAGAN (Centella asiatica) TERHADAP PERTUMBUHAN BAKTERI Pseudomonas aeruginosa - Siti Fatimah; Yuliana Prasetyaningsih; Sita Astuti Carmanyta (JFL : Jurnal Farmasi Lampung, 2021)
Pseudomonas aeruginosa is one of the bacteria that causes infectious diseases. These bacteria show resistance to several types of antibiotics, therefore it is necessary to do alternative treatment using natural ingredients. Pegagan (Centella asiatica) leaves contain active substances such as saponins, tannins, alkaloids and flavonoids that function as antibacterial. This study aims to determine the antibacterial effectiveness of pegagan leaf extract (Centella asiatica) against the growth of Pseudomonas aeruginosa bacteria. This type of research is an experimental study with the disc diffusion method. Pegagan leaves were extracted by maceration method using 70% ethanol as a solvent. The pegagan extract obtained was then diluted using sterile distilled water at concentrations of 20%, 40%, 60%, 80%, 100%. Positive control used Penicillin G 10 g and negative control used sterile distilled water. The results showed that pegagan leaf extract (Centella asiatica) with concentrations of 20%, 40%, 60%, 80% and 100% had an average diameter of inhibition zone against Pseudomonas aeruginosa 7,6 mm, 10 mm, 12 mm, 12,6 mm and 16 mm. Positive control (Penicillin G 10 g) of 22 mm and negative control (sterile distilled water) did not inhibit the growth of Pseudomonas aeruginosa bacteria. Pegagan extract at concentrations of 60%, 80% and 100% were effective in inhibiting the growth of Pseudomonas aeruginosa bacteria, while concentrations of 20% and 40% were not effective in inhibiting the growth of Pseudomonas aeruginosa bacteria. Â Keywords: Pseudomonas aeruginosa, Pegagan leaf extract, disc